Antioxidants as a defensive shield in thyme (Thymus vulgaris L.) grown on the soil contaminated with heavy metals - Kulbat, Kamila; Leszczyńska, Joanna (Biotechnology and Food Science, 2016)
The objective of this study was to investigate the effect of excessive concentration of selected heavy metals - nickel, copper and zinc on aromatic plants Thymus vulgaris. The present work examines the concentration of phenolic compounds, total antioxidant capacity and flavonoids content in leaves obtained from plants Thymus vulgaris grown on the soil contaminated with different concentration of these heavy metals. It was assumed, that selected metals, playing the role of micronutrients, cause toxic effect in their excessive concentrations, inhibit the growth and development of plants. Adverse impact on the plant is most likely due to the oxidative stress at a cellular level. It was demonstrated, that the lowest applied concentrations of heavy metals lead to the increased antioxidant content, which then decreases with increasing metal concentrations.